Molecular dynamics study of the effect of Calcium Ions on the thermostability of Bacillus amyloliquefaciens Phytase - Noorbatcha, Ibrahim Ali; Sultan, A. M.; Amid, Azura; Mohd. Salleh, Hamzah (2011)
Phytase is added to animal feeds to improve phosphorus absorption and reduce phosphorus excretion of swine and poultry. It hydrolyses phytate, which is a major form of storage of cereal grains and legumes in commercial animal feeds, into myo-inositol and inorganic phosphate. Adequate thermostability of phytase is necessary for field application as diets for swine and poultry are normally pelleted at high temperatures (60-80°C). In this study, Molecular Dynamics simulation (MD) was used to study the effect of calcium metal ions on the thermostability of Bacillus amyloliquefacience phytase. MD simulations of the enzyme with and without calcium ions were performed at 60°C and 80°C in water as the solvent medium, for duration of 2 ns. Root mean square deviations(RMSD) of backbone atoms are found to be lower in the presence of calcium ions at both the temperatures. In addition, RMSD values for individual residues of phytase at both calcium states and temperatures revealed that all residues that showed high RMSD values are located in turns or coils at the outer surface of the enzyme. As a result, these residues are the most susceptible to heating, hence produce high fluctuations.